Remineralization and fluoride uptake of white spot lesions under dental varnishes. (5th August 2020) - Shen, P; McKeever, A; Walker, GD; Yuan, Y; Reynolds, C; Fernando, JR; Chen, Y‐Y; MacRae, CM; Schneider, P; Reynolds, EC
Abstract: Introduction: The aim of this study was to evaluate white spot lesion (WSL) remineralization and fluoride uptake by the application of fluoride varnishes directly onto artificial WSLs in vitro . Methods: MI varnish containing casein phosphopeptide–amorphous calcium phosphate (CPP‐ACP) and 2.26% fluoride and Duraphat varnish containing 2.26% fluoride (no added calcium) were compared with a placebo varnish (no added calcium or fluoride). Two WSLs were prepared in enamel slabs and varnish applied to cover one of the two lesions. Each slab was immersed in artificial saliva for 14 days at 37°C. Mineral content was determined using transverse microradiography and fluoride uptake using electron probe microanalysis. The data were statistically analysed using a linear mixed model. Results: Both MI and Duraphat varnishes significantly remineralized the covered and uncovered WSLs when compared with the placebo varnish ( P  < 0.001). The WSLs covered with varnish showed greater remineralization than those uncovered. MI varnish produced the highest level of remineralization and significantly greater fluoride uptake (0.44 ± 0.08 wt%) compared with Duraphat (0.24 ± 0.03 wt%) and the placebo varnish (0.06 ± 0.05 wt%). Conclusion: Varnish containing fluoride and CPP‐ACP was superior to varnish containing fluoride alone in promoting WSL remineralization and fluoride uptake.